2020
DOI: 10.1038/s41598-020-59638-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of maca (Lepidium meyenii Walp.) plants to UV radiation in its high-altitude mountain ecosystem

Abstract: Ultraviolet (UV) radiation is a small fraction of the solar spectrum, which acts as a key environmental modulator of plant function affecting metabolic regulation and growth. Plant species endemic to the Andes are well adapted to the harsh features of high-altitude climate, including high UV radiation. Maca (Lepidium meyenii Walpers) is a member of Brassicaceae family native to the central Andes of peru, which grows between 3500 and 4500 m of altitude, where only highland grasses and few hardy bushes can survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Increased altitude leads to an intensification of integrated adversity stress consisting of multiple adversities such as UV radiation, low temperature, and hypoxia [ 63 , 64 , 65 ]. Excessive production of reactive oxygen species (ROS), such as H 2 O 2 and O 2 ·− , leads to oxidative stress [ 66 ], which induces the emergence of protein carbonylation and lipid peroxidation as indicated by Malondialdehyde (MDA) [ 67 , 68 , 69 ], which together indicate the level of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased altitude leads to an intensification of integrated adversity stress consisting of multiple adversities such as UV radiation, low temperature, and hypoxia [ 63 , 64 , 65 ]. Excessive production of reactive oxygen species (ROS), such as H 2 O 2 and O 2 ·− , leads to oxidative stress [ 66 ], which induces the emergence of protein carbonylation and lipid peroxidation as indicated by Malondialdehyde (MDA) [ 67 , 68 , 69 ], which together indicate the level of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Alpine habitats exhibit specific properties of integrated adversities such as strong radiation, oxygen deprivation, alpine cold, freezing and thawing, as well as regional-specific constraints on green vegetation cover [ 63 , 64 , 65 ]. Therefore, investigating plant changes in alpine habitats will provide a direct and effective way to understand plant change mechanisms from a holistic perspective and systemic cognitive level.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of organisms that live at very high elevations are relevant for understanding how species acclimate and adapt to high UV irradiances under extreme environmental conditions. For example, Maca ( Lepidium meyenii ) is a crop from the high Andes in Peru that can quickly recover from stress induced by acute high solar UV radiation [ 162 , 163 ]. Similarly, Chinese tallow trees ( Triadica sebifera ), growing in southern China, accumulate more UV-absorbing flavonoids in their leaves with increasing elevation (100 to 1000 m above sea level) [ 161 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…In plants, UV-B can induce detrimental or beneficial effects by the activation of UV-B-specific and/or -nonspecific signaling pathways depending on the energy level, exposure time, acclimation, peak wavelength, plant species, varieties and growth stages, and interaction with other environmental factors [ 4 , 5 , 6 ]. Previous studies have shown that high doses of UV-B can induce massive production of reactive oxygen species (ROS), which stimulates the production of hormones (i.e., jasmonic acid (JA) and salicylic acid (SA)) and triggers a general defense response [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%